Perancangan User Experience Aplikasi Web Self Service Kedai Om Kopi Menggunakan Pendekatan Human-Centered Design (HCD) - Dhaneswara Mursito Rukmi; Satrio Hadi Wijoyo; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The era of technological development is growing rapidly so that it has a big role in the business world, one of which is the coffee shop business. Therefore, Om Kopi wants to participate in existing developments, namely providing new services in the form of self-service. So, to realize these services, it is necessary to design a user experience for web applications for users. The design uses a human centered design (HCD) approach, in which the approach focuses on humans. The human focus in this study is users and stakeholders. Therefore, there are several stages in the solution development process. The stage of analyzing the context of use and user needs where the results are based on interviews with Om Kopi's stakeholders, employees and customers. So that these stages get information on web application users, namely employees and customers with their respective characteristics and duties. The design stage of the solution design produces a wireframe, screenflow, and high fidelity prototype. The evaluation stage uses a user experience questionnaire (UEQ). The evaluation of the web application obtained a mean value with a mean of 1.917 for attractiveness, 1,934 for perspicuity, 1,824 for efficiency, 1,912 for dependability, 1,728 for stimulation, and 0,978 for novelty. To increase the mean scale, improvements were made and recommended the features most desired by the user. From the results of the improvement experienced a significant increase.